Analisis Pengaruh Investasi Asing Langsung, Investasi Dalam Negeri Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2014-2023 - Abdul Hamid Shahab; Muhammad Alwi; Gusti Ayu Arini (Jurnal Riset Multidisiplin Edukasi, 2025)
Economic growth refers to the increase in the production capacity of a country, measured by the rise in Gross Domestic Product (GDP). When the economy grows, people's purchasing power increases, which encourages further consumption and creates a positive multiplier effect. This study aims to analyze the impact of independent variables (Foreign Direct Investment, Domestic Investment, and Labor) both partially and simultaneously on the dependent variable (Economic Growth) in Indonesia from 2014 to 2023. This research uses time series data on Foreign Direct Investment, Domestic Investment, and Labor over 10 years. Additionally, this study employs multiple linear regression analysis as the analytical tool. The results of this study show that the variables (Foreign Direct Investment, Domestic Investment and Manpower have a positive effect on economic growth in Indonesia. The Foreign Investment variable has a significant effect while the Domestic Investment and Labor variables have no significant effect and simultaneously or together the foreign direct investment, domestic investment and labor variables have a significant effect on economic growth (GDP) in Indonesia for the 2014-2023 period.